Hydrogen production from 2-propanol over Pt/Al2O3 and Ru/Al2O3 catalysts in supercritical water - Karakus, Yagmur; Aynaci, Fatih; Kipcak, Ekin; Akgun, Mesut (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
One of the alternative energy sources to fossil fuels is the use of hydrogen as an energy carrier, which provides zero emission of pollutants and high-energy efficiency when used in fuel cells, hydrogen internal combustion engines (HICE) or hydrogen-blend gaseous fueled internal combustion engines (HBICE). The gasification of organics in supercritical water is a promising method for the direct production of hydrogen at high pressures, with very short reaction times. In this study, hydrogen production from 2-propanol over Pt/Al2O3 and Ru/Al2O3 catalysts was investigated in supercritical water. To investigate the influences on hydrogen production, the experiments were carried out in the temperature range of 400 -550 degrees C and in the reaction time range of 10-30 s, under a pressure of 25 MPa. In addition, different 2-propanol concentrations and reaction pressures were tested in order to comprehend the effects on the gasification yield and hydrogen production. It was found that Pt/Al2O3 catalyst was much more selective and effective for hydrogen production when compared to Ru/Al2O3. During the catalytic gasification of a 0.5 M solution of 2-propanol, a hydrogen content up to 96 mol% for a gasification yield of 5 L/L feed was obtained. Copyright (C) 2013, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: 2-propanol; Catalytic gasification; Hydrogen; Supercritical water; HYDROTHERMAL GASIFICATION; BIOMASS; CELLULOSE; GLUCOSE; OXIDATION; ETHANOL; WASTE; Chemistry; Electrochemistry; Energy & Fuels